INTERPRETATION OF THE MAQASIDI IN ENVIRONMENTAL DISCOURSE: BUILDING PARADIGM OF THE HIFZ AL-BI'AH IN THE SOCIETY 5.0 ERA (International Conference on Social and Islamic Studies, 2021)
The data presented by the IPPC (Intergovernmental Panel on Climate Change) sends a warning signal to humanity. That humanity is in danger for the next 20 years is caused by global warming. So, how is the relationship between technological advances in solving these problems? On the one hand, we are facing the era of society 5.0 which is an era where technology is part of life itself so that technology no longer stops at mere informants. On the other hand, we lack the value of humanity itself, in this case, regarding the relationship between humans and their natural environment or in the term of Islamic studies referred to as hifz bi'ah. In this nuance of confusion, Tafsir Maqasidi issued New Fundamental Values of Qur'anic Ecology to maintain balance, both in the realm of epistemology and ontology. This study uses qualitative data, namely library research and uses a historical-philosophical approach as a means of building critical reasoning. The results of this study indicate that building the hifz al-Bi'ah paradigm through the construction of a new fundamental of Qur'anic Maqasidi in the Society 5.0 era is a necessity, so that explicitly (Maqasid Dhzahir) min kharij an-nusus, namely environmental verses (Hifz al-Bi'ah) is part of the responsibility as caliph al-'Ard as well as a guardian of the trust in the discourse of trilogy relations (God, the Universe, Humans), while implicitly (Maqasid Bathin) min dakhil an-nusus, namely the value of al'Adalah wa al-Musawah (justice), al-ukhwah al-insaniyyah ma'a al-bi'ah which reflects the attitude of al-wasathiyyah (balance). For this reason, on the one hand, the era of society 5.0 with part of life technology has brought many conveniences to human life, especially protecting the environment, on the other hand, it has also brought a new spirit for Muslim scholars to research further. Ayatul bi'ah with various perspectives so that values are obtained and then applied in everyday life.